Pengelolaan Perpustakaan Berbasis Teknologi di Perpustakaan Sma Negeri 1 Padang (Studi Kasus: Pada Perpustakaan Sma Negeri 1 Padang) - Putri, Oza Rahmadita; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractThe writing of this paper aims to describe how to process tecnologi digital-based collections, to describe how to manage information technology-based technology services, describing what are the facilities and infrastructure of technology library-based management at the Padang 1 Public High School Library. Data was collected through observation and interviews with librarians and visitors at the Padang 1 Public High School Library. Data analysis was carried out descriptively. Based on the discussion described above, it can be concluded that First, digital-based collection processing is processing physical collections in the form of systematic collection of collections ranging from checking library materials to compiling books on a shelf, processing book collections into digital collections using SLiMS applications, processing physical data collection of digital-based books by transferring media collections of books to digital-based collections by using a scanner machine. Second, the management of technology-based information services, namely the creation of membership cards, on the membership card library has information about member identities, member names, identity numbers, addresses and telephone numbers of users, information search services, application of corner literacy services. Third, library-based infrastructure management tools, namely infrastructure literacy corner bookshelves provided by schools, the application of barcode scanners, library building infrastructure that is quite extensive as a forum for educational information services in libraries, television facilities as learning media for students in Padang 1 Public High School and internet-connected computer facilities.Keywords: management; processing; technology